Enterprise, Business-Process and Information Systems Modeling: 22nd International Conference, BPMDS 2021, and 26th International Conference, EMMSAD 2021, Held at CAiSE 2021, Melbourne, VIC, Australia, June 28-29, 2021, Proceedings - Augusto, Adriano; Gill, Asif; Nurcan, Selmin; Reinhartz-Berger, Iris; Schmidt, Rainer; Zdravkovic, Jelena (Lecture Notes in Business Information Processing, 2021)
This book contains the proceedings of two long-running events held along with the CAiSE conference relating to the areas of enterprise, business-process and information systems modeling: * the 22nd International Conference on Business Process Modeling, Development and Support, BPMDS 2021, and * the 26th International Conference on Exploring Modeling Methods for Systems Analysis and Development, EMMSAD 2021.The conferences were planned to take place in Melbourne, Australia, during June 28-29, 2021, but changed to an online format due to the COVID-19 pandemic.For BPMDS 10 full papers and 1 short paper were carefully reviewed and selected for publication from a total of 26 submissions; for EMMSAD 13 full papers and 1 short paper were accepted from 34 submissions.The papers were organized in topical sections as follows:BPMDS: Improving event data quality in coherence with business requirements; enhancing the value of data in processes improvement; event stream and predictive monitoring; modeling languages and reference models;EMMSAD: Enterprise modeling; handling models and modeling methods; threat and evidence modeling; and model-driven engineering and applications.